Hipossuficiência dos proprietários de terra frente à instalação de parques eólicos na área rural do município de Santa Luzia - PB - Damasceno, Laura Emília Beatriz Lourenço (2023)
The global shift in economic exploration has prompted a worldwide need for diversification in the electric power matrix, aiming to make it cleaner and reduce environmental challenges. This led to the emergence of renewable energies, among them, wind energy. The municipality of Santa Luzia, situated in the mesoregion of Planalto da Borborema, Paraíba, has garnered attention for substantial investments in the wind energy sector. This attention is a result of investors focusing on the Northeast, attracted by the region's favorable climatic conditions. However, despite its prominent position in the Brazilian energy matrix, the cleanliness of an energy source goes beyond the absence of fossil fuels; it encompasses legal and socio-environmental impacts arising from the installation and execution of energy-capturing projects in their surroundings. Among the primary conflicts stemming from wind park installations in the city are those originating from lease agreements between companies and landowners, often exposed to abusive contractual clauses. This study analyzes the wind energy park installation process, examining contracts executed in Santa Luzia - PB through the lens of Marx's concept of land rent. The objective is to demonstrate how lease agreements and similar arrangements leave landowners unprotected while disproportionately favoring companies. The study also explores the local population's perception of the arrival of wind energy projects and highlights the main impacts of wind park installations in the region. The research utilizes literature review and documentary research to showcase the landowners' vulnerability in the lessor-lessee relationship, proposing adjustments to promote a more equitable contractual relationship.